Psychotropic medication before and after disability retirement by pre-retirement perceived work-related stress - Halonen J.I.; Chandola T.; Hyde M.; Leinonen T.; Westerlund H.; Aalto V.; Pentti J.; Laaksonen M.; Stenholm S.; Mänty M.; Vahtera J.; Oksanen T.; et al. (United Kingdom, 2022)
Register-based date and diagnosis of disability retirement of 2766 participants of the Finnish Public Sector study cohort were linked to survey data on ERI, social- and health-related covariates, and to national records on prescribed reimbursed psychotropic medication, measured as defined daily doses (DDDs). Follow-up for DDDs was 2-5 years before and after disability retirement. We assessed differences in the levels of DDDs before and after retirement among those with high vs. low level of pre-retirement ERI with repeated measures regression.
Retirement has been associated with improved mental health, but it is unclear how much this is due to the removal of work-related stressors. We examined rates of psychotropic medication use before and after the transition to disability retirement due to mental, musculoskeletal and other causes by pre-retirement levels of perceived work stress (effort-reward imbalance, ERI).\nThe level of psychotropic medication use over the transition to disability retirement due to mental, but not musculoskeletal or other, causes was modified by pre-retirement perceived work-related stress. This suggests that among people retiring due to mental disorders those who had stressful jobs benefit from retirement more than those with low levels of work-related stress.
Those with high (vs. low) levels of ERI used slightly more psychotropic medication before disability retirement due to mental disorders [rate ratio (RR) 1.14, 95% confidence intervals (CI) 0.94-1.37], but after retirement this difference attenuated (RR 0.94, 95% CI 0.80-1.10, P for interaction 0.02). Such a change was not observed for the other causes of disability retirement.